2019
DOI: 10.1186/s13643-019-0969-9
|View full text |Cite
|
Sign up to set email alerts
|

Gender-based violence among female youths in educational institutions of Sub-Saharan Africa: a systematic review and meta-analysis

Abstract: Background Gender-based violence is a public health issue. The prevalence of gender-based violence is high in Sub-Saharan Africa. Therefore, this study aims to produce an overall summary estimate on the prevalence of gender-based violence according to different types and its risk factors among female youths in educational institutions of Sub-Saharan Africa. Methods Studies published in English between 2000 and 2017 were identified by searching electronic databases such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
69
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 45 publications
12
69
7
1
Order By: Relevance
“…Overall, a high pooled prevalence of IPV among women in SSA was found as compared to the global estimate which was conducted in 56 countries in 2013 [4] and SSA countries [5,21,102,103]. The findings of this review are comparable or slightly higher to studies conducted in 14 SSA countries [27,102]. The higher prevalence of IPV in our study could provide a better overview compared to previous studies where the number of countries involved were relatively small.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Overall, a high pooled prevalence of IPV among women in SSA was found as compared to the global estimate which was conducted in 56 countries in 2013 [4] and SSA countries [5,21,102,103]. The findings of this review are comparable or slightly higher to studies conducted in 14 SSA countries [27,102]. The higher prevalence of IPV in our study could provide a better overview compared to previous studies where the number of countries involved were relatively small.…”
Section: Discussionsupporting
confidence: 63%
“…In this review, the pooled prevalence of all types of GBV, physical, sexual and emotional violence were consistently higher in SSA countries as compared to many other regions in the world [25,102,103]. Emotional violence was the most prevalent reported type of violence.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…A WHO study based on 10 countries reported women experiencing 15% to 71% physical or sexual violence or both, and 20% to 75% faced emotional abuse. 2 Because of IPV, women have become more vulnerable towards physical injury and mental health illnesses, leading to an increased risk of suicidal tendencies. 3 Although a global concern, developing countries are more susceptible to the problems caused by IPV.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and Meta-Analysis in Gender-based violence among female youths in Sub-Saharan Africa revealed that the overall prevalence of gender-based violence ranged from 42.3% in Nigeria to 67.7% in Ethiopia. The lifetime prevalence of sexual violence ranged from 4.3 to 76.4% and physical violence ranged from 7.4 to 66.1% [17]. Information related to magnitude of all forms of violence specific to street children is still vacant globally that"s why the world fail to develop policies and intervene for visible problems of the street world , so does Ethiopia.…”
Section: Introductionmentioning
confidence: 99%